Incidence and Prevalence of Sexual Dysfunction in Women and Men: A Consensus Statement from the Fourth International Consultation on Sexual Medicine 2015. Issue 2 (1st February 2016) - McCabe, Marita P.; Sharlip, Ira D.; Lewis, Ron; Atalla, Elham; Balon, Richard; Fisher, Alessandra D.; Laumann, Edward; Lee, Sun Won; Segraves, Robert T.
ABSTRACT: Introduction: The incidence and prevalence of various sexual dysfunctions in women and men are important to understand to designate priorities for epidemiologic and clinical research. Aim: This manuscript was designed to conduct a review of the literature to determine the incidence and prevalence of sexual dysfunction in women and men. Methods: Members of Committee 1 of the Fourth International Consultation on Sexual Medicine (2015) searched and reviewed epidemiologic literature on the incidence and prevalence of sexual dysfunctions. Key older studies and most studies published after 2009 were included in the text of this article. Main Outcome Measures: The outcome measures were the reports in the various studies of the incidence and prevalence of sexual dysfunction among women and men. Results: There are more studies on incidence and prevalence for men than for women and many more studies on prevalence than incidence for women and men. The data indicate that the most frequent sexual dysfunctions for women are desire and arousal dysfunctions. In addition, there is a large proportion of women who experience multiple sexual dysfunctions. For men, premature ejaculation and erectile dysfunction are the most common sexual dysfunctions, with less comorbidity across sexual dysfunctions for men compared with women. Conclusion: These data need to be treated with caution, because there is a high level of variability across studies caused by methodologic differences in the instruments used to assess presence of sexual dysfunction, ages of samples, nature of samples, methodology used to gather the data, and cultural differences. Future research needs to use well-validated tools to gather data and ensure that the data collection strategy is clearly described.